Review - Flavins as photoreceptors of blue light and their spectroscopic properties - Grajek, Hanna (Current Topics in Biophysics, 2012)
This review describes 1) the development of studies on flavin photoreceptors as blue light photoreceptors in many living organisms: their kinds and functions; 2) the studies on spectroscopic properties of flavins, both their dimers and monomers; 3) nonradiative excitation energy transport in the presence of monomers and fluorescent/nonflurescent FMN dimers (excitation traps). The existence equilibrated luminescent FMN centers, energy migration and excitation sink to FMN dimers are taken into account.